Students’ experiences of fairness in online assessment: A phenomenological study in a higher education institution context - Eltahir, Mohd Elmagzoub; Annamalai, Nagaletchimee; Uthayakumaran, Arulselvi; Zyoud, Samer H.; García, Antonia Ramírez; Mažeikienė, Viktorija; Zakarneh, Bilal Ibrahim; Al Salhi, Najeh Rajeh (SAGE Publications Inc., 2023)
Online assessment is a new introduction in many developing countries during the COVID-19 pandemic, including Malaysia, Lithuania, and Spain. The current study conducted a phenomenology study to probe insights about fairness in online assessment. The interview data were interpreted from the perspective of social psychology theory that emphasizes distributional, procedural, and interaction justice. The study selected participants through purposive sampling techniques. Distributional justice revealed that grading seems fair when students experience multiple assessments, clear rubrics, and effective feedback from lecturers. In distributional justice students experience injustice when there are unclear expectations of assessment. Regarding procedural justice, students’ unfairness was related to limited time, technical problems, and unclear assessment expectations. Interactional justice was related to privacy in communicating grades and weak interaction during the assessment. These results emphasize the importance of understanding the elements that influence students’ views of fairness and methods to improve assessment during online assessment in a university setting.